Pengembangan Ekonomi Islam di Pesantren Jawa Timur - Ahmad Fauzi (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2017)
This article aims to elaborate the value of local pesantren (Islamic boarding school) in Islamic economic development. The pesantren’s Islamic economics is assessed by using the Pierre Bourdieu's social practice theory of social action, namely (Habitus x Capital) + Ranah = Practice. In the theory of social practice, internalization of social values, interpreted as social capital in realizing the behaviour of Islamic economics (economic behaviour). The transformation of the value of local wisdom, believed to be able to inspire all the actions and social roles of individuals in the economic field by promoting the three basic pillars, among others: 1) ownership (al-milkiyah) according to sharia, 2) ownership use (tasharruffi al-milkiyah) and 3) distribution of community wealth (taui 'al-tsarwah baina al-nas) through mechanisms according to the system: shari'a, ai-ashlu fial-afdl' al-taqajyudu bi al-hukm al-syar'.